2001
DOI: 10.1107/s0108768101015403
|View full text |Cite
|
Sign up to set email alerts
|

Amino and cyano N atoms in competitive situations: which is the best hydrogen-bond acceptor? A crystallographic database investigation

Abstract: The relative hydrogen-bond acceptor abilities of amino and cyano N atoms have been investigated using data retrieved from the Cambridge Structural Database and via ab initio molecular orbital calculations. Surveys of the CSD for hydrogen bonds between HX (X = N, O) donors, NÐTÐ CN (push±pull nitriles) and NÐ (Csp 3 ) n ÐCN molecular fragments show that the hydrogen bonds are more abundant on the nitrile than on the amino nitrogen. In the push±pull family, in which T is a transmitter of resonance effects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…However, in the case of hydrogen‐bond formation between OH acids (another type of acid/base interaction) and cyano bases, a similar preference for association to the CN group has been reported 19. 20 If an amino group is either directly linked to the cyano function (cyanamides), or connected through a double bond (CC or CN), or by a benzene ring (1,4 positions), the strong conjugation between the electron‐donating nitrogen and the strong electron‐withdrawing cyano group induces the so‐called “push–pull effect”. These conclusions were reached from the analysis of crystallographic data, spectroscopic shifts, association‐constant measurements, and ab initio calculations 19.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…However, in the case of hydrogen‐bond formation between OH acids (another type of acid/base interaction) and cyano bases, a similar preference for association to the CN group has been reported 19. 20 If an amino group is either directly linked to the cyano function (cyanamides), or connected through a double bond (CC or CN), or by a benzene ring (1,4 positions), the strong conjugation between the electron‐donating nitrogen and the strong electron‐withdrawing cyano group induces the so‐called “push–pull effect”. These conclusions were reached from the analysis of crystallographic data, spectroscopic shifts, association‐constant measurements, and ab initio calculations 19.…”
Section: Resultsmentioning
confidence: 59%
“…These conclusions were reached from the analysis of crystallographic data, spectroscopic shifts, association‐constant measurements, and ab initio calculations 19. 20…”
Section: Resultsmentioning
confidence: 98%
“…The second approach uses a class of algorithms developed for the mathematical problem of paired comparison. [20][21][22][23][24] Paired comparison is widely used for ranking competitors in games such as chess, tennis and more recently, online multi-player computer games. The algorithms use the outcome of pairwise competitions to assign ratings to competitors.…”
Section: Approachmentioning
confidence: 99%
“…In both furan and esters, the ether-O is bonded to Csp 2 atoms and the relative weakness of Csp 2 ÐO as a hydrogen-bond acceptor has been extensively studied by Bo È hm et al (1998). More recently, the CSD has been used in conjunction with quantum chemical calculations to study competition between amino-N and cyano-N (Ziao et al, 2001), in which the latter is shown to be the more potent acceptor, and by Steiner (2001) to study acceptor competition for the strong carboxyl donor. A detailed understanding of acceptor competition and the effects of local acceptor environments are of vital importance in crystal engineering and studies of protein±ligand interactions.…”
Section: Hydrogen-bond Competition Effectsmentioning
confidence: 99%